SENSITIVITY ANALYSIS USING ADM1 MODEL FOR BIOGAS PRODUCTION - NAIR, Abhilash; ZUZA, Alexandrina; AGACHI, Paul-Şerban; DAS, Arpita; BREHAR, Marius Adrian; BARABÁS, Győző Ferencz (Studia Universitatis Babeș-Bolyai Chemia, 2015)
This study is showcasing a sensitivity analysis that would enable both experts and non-experts to understand the effects of various stoichiometric and kinetic parameters, input composition, carbon and nitrogen composition in the Anaerobic Digestion Model no. 1 (ADM1). The ADM1 has been modified based on the design parameters and process conditions in the WWTP of Cluj-Napoca. It has to be further calibrated to simulate the steady-state anaerobic digestion of activated sludge at municipal wastewater. For this purpose, it is extremely important to understand the effect of various model parameters on the output variables. The modified model is able to predict the output with 2% error in biogas flow rate and 10% error in the digester pressure. The sensitivity analysis performed identifies the parameters that have a major impact over the output. This report also presents a list of parameters that have to be modified to calibrate the ADM1 model.